ANALISIS PESAN MOTIVASI DALAM FILM “RENTANG KISAH” (PENDEKATAN TEORI ABRAHAM MASLOW) - Suci Ramadhani, Dela; Yoserizal Saragih, M; Fatra Deni, Indira (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
The purpose of this study is to find out how the motivational messages in the film "Range of Stories" are formed from the perspective of Abraham Maslow's Theory. This research uses qualitative research with a descriptive approach and Abraham Maslow's motivational theory approach. The data collection technique is by observing, documenting and studying the literature. The primary data source is film video recordings. The findings from this study are that there are five forms of motivation strata described by expert Abraham Maslow contained in the film "Range of Stories". 1) The first level of physiological needs there are five elements in the film that describe physiological needs; 2) The second stratum, there are two elements in this film that describe the need for a sense of security in the film; 3) The third stratum, there are two elements in this film that describe social needs (a feeling of affection or being loved); 4) The fourth stratum, there are two elements in this film which describe the need for recognition from others (ego); 5) In the fifth strata, there are two elements in this film that describe a form of self-actualization.